Union wage compression in a Right-to-Manage model - Thorsten Vogel (Humboldt University of Berlin, Collaborative Research Center 649 - Economic Risk, 2007)
Trade unions are consistently found to compress the wage distribution. Moreover, unemployment affects in particular low-skilled workers. The present paper argues that an extended Right-to-Manage model can account for both of these findings. In this model unions compress the wage distribution by raising wages of workers in low productivity industries (or low-skilled workers) above market clearing levels. Our analysis suggests that the most direct way to test this model would be via a test for stochastic dominance. We also allow for capital adjustments and compare union and non-union wage distributions in a general equilibrium framework.
Keywords: J51; J31; J41; J21; 330; Trade unions; wage compression; Lohnpolitik; Lohnstruktur; Ungelernte Arbeitskräfte; Gewerkschaftlicher Organisationsgrad; Arbeitslosigkeit; Lohnverhandlungstheorie; Theorie; OECD-Staaten